Imaging of Norway spruce early somatic embryos with the ESEM, Cryo-SEM and laser scanning microscope - Neděla, Vilém; Hřib, Jiří; Havel, Ladislav; Hudec, Jiří; Runštuk, Jiří (Micron (Oxford, England, 2016)
This article describes the surface structure of Norway spruce early somatic embryos (ESEs) as a typical culture with asynchronous development. The microstructure of extracellular matrix covering ESEs were observed using the environmental scanning electron microscope as a primary tool and using the scanning electron microscope with cryo attachment and laser electron microscope as a complementary tool allowing our results to be proven independently. The fresh samples were observed in conditions of the air environment of the environmental scanning electron microscope (ESEM) with the pressure from 550Pa to 690Pa and the low temperature of the sample from -18°C to -22°C. The samples were studied using two different types of detector to allow studying either the thin surface structure or material composition. The scanning electron microscope with cryo attachment was used for imaging frozen extracellular matrix microstructure with higher resolution. The combination of both electron microscopy methods was suitable for observation of "native" plant samples, allowing correct evaluation of our results, free of error and artifacts.
Keywords: semena rostlinná; Picea; konfokální mikroskopie; Cryoelectron Microscopy; Norway; smrk; Bright field/dark field microscopy; Cryo-SEM; ESEM; Seeds; Microscopy, Confocal; elektronová kryomikroskopie; Microscopy, Electron, Scanning; Picea abies; Norsko; Extracellular matrix; mikroskopie elektronová rastrovací; Somatic embryogenesis; nízká teplota; Cold Temperature